2018
DOI: 10.1002/nafm.10217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of a Habitat Suitability Model for Postdrift Larval Lake Sturgeon in the St. Clair and Detroit Rivers

Abstract: We evaluated composition and spatial distribution of riverine nursery habitat for larval Lake Sturgeon Acipenser fulvescens in the Middle Channel of the St. Clair River, Michigan, and Fighting Island Channel of the Detroit River, Ontario, using a habitat suitability model (HSM) and fish collections. Although model outputs indicated similar portions of high‐quality habitat in the Middle Channel (16.9%) and Fighting Island Channel (15.7%), larval abundance and dispersal patterns varied between these systems. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The juvenile lake sturgeon ‘hot spots’ identified were downstream of known lake sturgeon spawning locations, including constructed spawning reefs (Manny & Kennedy, 2002; Manny et al, 2015), which suggests connectivity between spawning and nursery areas in the St. Clair and Detroit rivers and could explain the spatial extent of ‘hot spots’. Krieger and Diana (2017) and Krieger et al (2018) found larval lake sturgeon in nursery habitat in the St. Clair and Detroit rivers close to spawning locations with catch rates diminishing with distance downstream. Barth et al (2011) also found that juvenile lake sturgeon in the Winnipeg River (50.1471 N, −95.8235 W) exhibit high natal site fidelity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The juvenile lake sturgeon ‘hot spots’ identified were downstream of known lake sturgeon spawning locations, including constructed spawning reefs (Manny & Kennedy, 2002; Manny et al, 2015), which suggests connectivity between spawning and nursery areas in the St. Clair and Detroit rivers and could explain the spatial extent of ‘hot spots’. Krieger and Diana (2017) and Krieger et al (2018) found larval lake sturgeon in nursery habitat in the St. Clair and Detroit rivers close to spawning locations with catch rates diminishing with distance downstream. Barth et al (2011) also found that juvenile lake sturgeon in the Winnipeg River (50.1471 N, −95.8235 W) exhibit high natal site fidelity.…”
Section: Discussionmentioning
confidence: 98%
“…ery areas in the St. Clair and Detroit rivers and could explain the spatial extent of 'hot spots' Krieger and Diana (2017). andKrieger et al (2018) found larval lake sturgeon in nursery habitat in the St. Clair and Detroit rivers close to spawning locations with catch rates diminishing with distance downstream Barth et al (2011). also found that juvenile lake sturgeon in the Winnipeg River (50.1471 N, −95.8235 W) exhibit high natal site fidelity.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…predation or starvation) while drifting downstream from spawning grounds (Waraniak, Baker, & Scribner, 2018). Larval dispersal and postdrift settlement studies have led to the identification of downstream river habitats that may increase growth and survival (Krieger, Young, & Diana, 2018).…”
Section: Introductionmentioning
confidence: 99%